2022
DOI: 10.1002/alz.12706
|View full text |Cite
|
Sign up to set email alerts
|

Test‐retest variability of plasma biomarkers in Alzheimer's disease and its effects on clinical prediction models

Abstract: Introduction:The effect of random error on the performance of blood-based biomarkers for Alzheimer's disease (AD) must be determined before clinical implementation. Methods:We measured test-retest variability of plasma amyloid beta (Aβ)42/Aβ40, neurofilament light (NfL), glial fibrillary acidic protein (GFAP), and phosphorylated tau (p-tau)217 and simulated effects of this variability on biomarker performance when predicting either cerebrospinal fluid (CSF) Aβ status or conversion to AD dementia in 399 non-dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 43 publications
4
34
0
Order By: Relevance
“…These performances are similar to several blood plasma p-tau immunoassays, and with rigorous stability that provides a benefit to aid in the diagnosis of AD. Further, results from Cullen et al ( 18 ) shown that combining BBM reduced the impact of assay variability on biomarker performance. Recently, it was shown that in cognitive impairment at the earliest stages of pathological amyloid accumulation, the combination of p-tau217 with Aβ42/40 may be more sensitive than p-tau217 alone for the detection of AD ( 23 ).…”
Section: State-of-scientific Development Of Blood-based Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…These performances are similar to several blood plasma p-tau immunoassays, and with rigorous stability that provides a benefit to aid in the diagnosis of AD. Further, results from Cullen et al ( 18 ) shown that combining BBM reduced the impact of assay variability on biomarker performance. Recently, it was shown that in cognitive impairment at the earliest stages of pathological amyloid accumulation, the combination of p-tau217 with Aβ42/40 may be more sensitive than p-tau217 alone for the detection of AD ( 23 ).…”
Section: State-of-scientific Development Of Blood-based Markersmentioning
confidence: 99%
“…An increase of only 5% in coefficient of variability impacted its accuracy for discriminating amyloid positive PET versus negative cases. Cullen et al measured the test-retest variability (random effect) of blood Aβ42/Aβ40 ratio, NfL, GFAP, and p-tau217 from the Biomarkers For Identifying Neurodegenerative Disorders Early and Reliably (BioFINDER) -1 study (n=399) ( 18 ). In this study, the test-retest variability reduced the performance of biomarkers for predicting abnormal amyloid accumulation and progression to AD dementia.…”
Section: State-of-scientific Development Of Blood-based Markersmentioning
confidence: 99%
“…In a recent study, even within carefully controlled visits by the same researchers only 6-10 weeks apart, there was 20% or more test-retest variability of plasma P-tau217, neurofilament light, and glial fibrillary acidic protein. 30 In a person who might undergo sampling years apart by different practitioners, pre-analytical variation will vary even more than this. While the NT1-tau values from the discovery cohort predicted the values in the validation cohort (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…(1) The test-retest reliability of the test should be evaluated systematically for all biomarkers and combinations thereof. 36 In our sample, we could only evaluate test-retest stability of two biomarkers (p-tau 181 and NfL), considering only analytical and postanalytical variables. Indeed, the test-retest variability shown here is an underestimation, as we tested twice samples that were collected at the same blood withdrawal, and thus our estimates did not take into account many other variables that can affect plasma biomarkers, such as concomitant medications and physiological and pathological conditions.…”
Section: Neurodegenerationmentioning
confidence: 99%